2013
DOI: 10.1002/2013ja019261
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of 2010 high‐mountain (Tien‐Shan) experiment on observations of thunderstorm‐related low‐energy neutron emissions

Abstract: [1] The high-mountain experiment in a thunderstorm atmosphere, in which "extraordinary high flux of low-energy neutrons" was detected, is analyzed. Due to the lack of data on the radiation source, we do not analyze directly measured absolute count rates. Instead, we address the experimental configuration, namely, simultaneous measurements by shielded and unshielded helium counters, which allow a comparison of relative count rates and, thus, verifying the species of the detected radiation. Results of Monte Carl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…There may be short spikes inside the 2 min averaged count rate increases. Also, other authors indicate relations between atmospheric discharge and short time increases of neutrons (including thermal ones) at the same site (e.g., Babich et al, 2013;Kozlov et al, 2013;Martin & Alves, 2010;Starodubtsev et al, 2012;Tsuchiya et al, 2012). Recording time of each pulse, as well as anticoincidence between different channels of SEVAN, now in progress, may help in clarification.…”
Section: 1002/2016jd026439mentioning
confidence: 95%
“…There may be short spikes inside the 2 min averaged count rate increases. Also, other authors indicate relations between atmospheric discharge and short time increases of neutrons (including thermal ones) at the same site (e.g., Babich et al, 2013;Kozlov et al, 2013;Martin & Alves, 2010;Starodubtsev et al, 2012;Tsuchiya et al, 2012). Recording time of each pulse, as well as anticoincidence between different channels of SEVAN, now in progress, may help in clarification.…”
Section: 1002/2016jd026439mentioning
confidence: 95%
“…In view of the shortcomings in Babich and Roussel‐Dupré () and given new experimental (Briggs et al, ; Chilingarian et al, , , , , ; Connaughton et al, ; Cummer et al, , ; Gurevich et al, ; Ishtiaq et al, ; Kelley et al, ; Kuroda et al, ; Marisaldi, Fuschino et al, ; Marisaldi, Tavani et al, ; Martin & Alves, ; Starodubtsev et al, ; Tavani et al, ; Tsuchiya et al, , , , ) and computational (Babich, ; Babich et al, , ; Babich, Bochkov, Kutsyk et al, ; Babich, Bochkov, Donskoĭ et al, ; Babich, Bochkov, Kutsyk et al, ; Babich, Bochkov, Dwyer et al, ; Babich et al, ; Carlson et al, ; Celestin, Xu, & Pasko, ; Dwyer, ; Dwyer, Grefenstette, & Smith, ; Kelley et al, ; Tsuchiya et al, ; Xu, Celestin, & Pasko, ) data on thunderstorm γ rays and neutrons, reanalyzing of the problem of the C614 production by thunderstorms is expedient. The new analysis is based not on a limited number of detections of thunderstorm neutrons as in Babich and Roussel‐Dupré () but on a vast amount of new data obtained from detecting of thunderstorm ground enhancements, i.e., enhanced fluxes of high‐energy electrons, hard γ rays, and neutrons on the Earth's surface, which have been copiously collected on Mount Aragats, Armenia (3250 m above sea level) (Chilingarian et al, , , , , ) and at other sites worldwide: Japan (sea level and 2770 m above sea level) (Tsuchiya et al, , , ); Tibet, China (4300 m above sea level) (Tsuchiya et al, ); Himalayas, India (2743 m above sea level) (Ishtiaq et al, ; Shah et al, ); and Tien Shan, Kazakhstan (3340 m above sea level) (Gurevich et al,…”
Section: History Of the Problemmentioning
confidence: 99%
“…It is pertinent to note that, as ranges of photons with energies ε γ ≥ ε th,N greatly exceed transverse sizes of lightning channels, the neutron‐producing reactions occur outside the channels (Babich, ; Babich, Bochkov, Kutsyk et al, ; Babich, Bochkov, Dwyer et al, ; Babich et al, ). The neutron pulses may only correlate with lightning EMPs; rather frequently, they occur in advance of them or even do not correlate with them.…”
Section: History Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Further measurements were performed [ Shyam and Kaushik , ; Bratolyubova‐Tsulukidze , ; Tsuchiya et al , ; Kozlov et al , , and references therein] enhancing the present knowledge about these phenomena. However, Babich et al [, , ] have shown that the counters in these experiments have been sensitive also to other ionizing emissions. More reliable observations were performed by Chilingarian et al [, ].…”
Section: Introductionmentioning
confidence: 99%